Який препарат з групи похідних сульфанілсечовини додати до метформіну? - Юзвенко, Т. Ю.; Зуєв, К. О.; Когут, Д. Г. (Clinical Endocrinology and Endocrine Surgery, 2012)
Current views on combination therapy of diabetes mellitus type 2 on the basis of analysis of the results of large multicenter studies are discussed in a lecture.